Monogamy: Cause, Consequence, or Corollary of Success in Wild Canids? - Macdonald, David W.; Campbell, Liz A. D.; Kamler, Jan F.; Marino, Jorgelina; Werhahn, Geraldine; Sillero-Zubiri, Claudio (Frontiers in Ecology and Evolution, 2019)
The Canidae are successful, being a widespread, abundant, speciose, and adaptable family. Several canids in particular have recently experienced rapid expansions in range and abundance, with similar situations mirrored on several continents by different species. Despite extreme behavioural diversity between and within species, monogamy is a common denominator in canid societies. In this review, we ask why canids are monogamous and how monogamy is related to their success. We begin with an overview of canid social monogamy, describing the pair bonding, paternal care, and often alloparental care that is characteristic of the family, and discuss theories on the evolution of mammalian social monogamy. We discuss why and how monogamy is maintained in canids, either voluntarily or enforced, and how ecological conditions influence either the functional advantages of monogamy or ability for enforcement and thus whether social monogamy is maintained. Social monogamy does not necessitate exclusive mating and many canids exhibit extra-pair paternity. We consider the costs and benefits of extra-pair mating for male and female canids and how ecological conditions can shift this cost/benefit balance and thus affect its prevalence. Monogamy may be responsible for many of the unusual reproductive characteristics of canids through facilitating alloparental care and monogamy enforcement, and the domestic dogs’ departure from monogamy supports our interpretation that it is an adaptation to resource availability. In asking whether monogamy is responsible, at least in part, for their success, we propose the monogamy as pro-cooperative hypothesis, suggesting four characteristics have contributed to canid success: 1. ecological flexibility, 2. high mobility, 3. high reproductive rates, and 4. sociality/cooperation, with the latter two being consequences of monogamy. These four interconnected traits enhance one another and it is their combination, with monogamy at its foundation enabling cooperative sociality and thereby enhanced reproduction and survival, that together comprise the formula of canid success.